The Caribbean - Evans, Lancelot O; Caribbean & West Indies (Sterling Publishing Co., Inc., 1979)
Reviews the history, government, geography, economy, and way of life of the Bahamas, Virgin Islands, Barbados, Trinidad, and Tobago, and other English-speaking islands of the Caribbean.
Keywords: Caribbean & Latin America; Juvenile Nonfiction; People & Places; Travel